Media Sosial Instagram Sebagai Sarana Dakwah Di Kalangan Mahasiswa - Febriyani, Siti Aisyah Artina; Rizki, Juni Wati Sri; Siregar, Nurfitriani M. (Hikmah, 2024)
AbstractThis research was made with the aim of seeing what kind of use of social media instagram as a means of da'wah and what are the reasons for students of the Islamic Communication and Broadcasting Study Program, class of 2020-2021, Faculty of Da'wah and Science.Islamic Communication and Broadcasting Study Program class of 2020-2021 Faculty of Da'wah and Science Communication State Islamic University Sheikh Ali Hasan Ahmad Addary Padangsidimpuan. The method used used in this study is descriptive qualitative using a phenomenological approach.  analysis used in this research is the Uses and Gratifications theory. Gratifications theory. The results of this study show that students use Instagram as a means of da'wah. In the process of using Instagram as a means of da'wah, it can be in the form of stories with captions containing preaching messages, reposting preaching messages through instastory, and uploading photos or videos with captions that contain preaching messages. The underlying reason for students. Students of the Islamic Communication and Broadcasting Study Program use Instagram social media as a means of da'wah is that Instagram displays interesting features, a fairly wide range, and a wide range of social media, features, a fairly wide range, and Instagram is not bound by time is not bound by time. Keywords: Means of Da’wah, Students,Social Media, Instagram AbstrakPenelitian ini dibuat dengan tujuan untuk melihat seperti apa penggunaan media sosial instagram dijadikan sebagai sarana dakwah dan apa saja alasan Mahasiswa Program Studi Komunikasi dan Penyiaran islam angkatan 2020-2021 Fakultas Dakwah dan Ilmu Komunikasi Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan. Metode yang digunakan dalam penelitian ini yaitu deskriptif kualitatif dengan menggunakan pendekatan fenomenologi. Pisau analisis yang digunakan dalam penelitian ini adalah teori Uses and  Gratifications. Hasil penelitian ini menunjukkan bahwa mahasiswa  menggunakan Instagram sebagai sarana dakwah. Dalam proses penggunaannya Instagram sebagai sarana dakwah dapat berupa story dengan caption yang memuat pesan dakwah, merepost pesan dakwah melalui instastory, dan menggungah foto atau video dengan caption yang memuat pesan dakwah. Alasan yang mendasari Mahasiswa Program Studi Komunikasi dan Penyiaran Islam menggunakan media sosial Instagram sebagai sarana dakwah ialah Instagram menampilkan fitur yang menarik, jangkaun yang cukup luas, dan Instagram tidak terikat oleh waktu. Kata kunci: Sarana Dakwah, Mahasiswa, Media Sosial, Instagram